Urgensi Asbabun Nuzul dalam Mengatasi Pemahaman Takfiri: Kajian Ayat-ayat Takfir dalam Al-Qur'an - Andri Syahputra; Agustiar Agustiar (Al-Amin: Jurnal Ilmu Pendidikan dan Sosial Humaniora, 2023)
Asbab al-nuzul is a study in the science of the Qur'an that contains the reason for the descent of a verse in the Qur'an. A verse cannot be understood correctly unless it is understood by understanding the principle of the descent of the verse. So by reviewing in terms of asbab nuzul a verse will provide an explanation of the law. One verse that is often debated is related to takfir which affects the understanding of takfirism by some groups. This starts from understanding textuality in takfir verses without looking at the contextuality of the verse and its asbab an-nuzul. So how important is the knowledge of asbab an-nuzul in interpreting takfir verses in the Qur'an. The purpose of this study is to find out how the correct understanding of takfir verses in the Qur'an actually is. The research method used is qualitative research that is descriptive analysis using literature review. The results of this study answer that knowing asbab an-nuzul ayat al-Qur'an can be a solution to overcome takfirism